APPLICATION OF INDEX CARD MATCH MODEL IN THE THEMATIC LEARNING OF CLASS IV STATE SD 06 SRIKATON STUDENTS - Kiki Yulia Silpiani; Tio Gusti Satria; Elya Rosalina (Literasi Nusantara, 2020)
With the research samples taken the entire number of grade IV elementary School 06 Srikaton is grade IV which amounted to 18 students. The data collection is done by test techniques in the form of essays amounting to 10 items. The Data collected in the analysis uses one sample test-z. Based on data analysis, can be deduced the results of the thematic learning outcomes of grade IV Elementary School 06 Srikaton year lesson 2020/2021 after applying the index card match model significantly completed. The average thematic learning results of (78,28) percentage of students that reached a total of 83%. can be deduced the results of the thematic learning outcomes of grade IV Elementary School 06 Srikaton year lesson 2020/2021 after applying the index card match model significantly completed. The average thematic learning results of (78,28) percentage of students that reached a total of 83%. can be deduced the results of the thematic learning outcomes of grade IV Elementary School 06 Srikaton year lesson 2020/2021 after applying the index card match model significantly completed. The average thematic learning results of (78,28) percentage of students that reached a total of 83%.